KOMUNIKASI INTRAPERSONAL PADA LIRIK LAGU “SENYUMLAH” KARYA ANDMESH KAMALENG SEBAGAI MOTIVASI HIDUP - Juliansyah, Juliansyah (Fakultas Dharma Duta, 2024)
Abstrac Intrapersonal communication refers to the communication process that occurs within a person, involving personal thoughts, feelings, and reflections. The process of managing information in intrapersonal communication goes through several stages, namely sensation, perception, memory, and thinking. Sensation is the process of capturing stimuli. Perception is the process of giving meaning to sensations so that humans gain new knowledge. So that perception turns sensation into information. Memory is the process of storing information and recalling it. Thinking is processing and manipulating information to meet needs or provide a response. So that intrapersonal communication can serve as a foundation for good decision making and positive social interactions. One way that intrapersonal communication can be the foundation for good decision-making is by listening to music and understanding song lyrics, especially those that can make a person get motivated and more excited in living his life. The lyrics of the song “Senyumlah” by Andmesh Kamaleng, not only offer interesting melodies and music, but also have a deep motivational message. The occurrence of intrapersonal communication of Andmes Kamaleng so that he is able to write and string word by word so that it becomes song lyrics in several stanzas containing words full of gratitude and motivation so that it raises high self-efficacy. This research utilizes the theory of self-efficacy and uses the literature study method. The results showed that the lyrics of the song “Senyumlah” function as a source of motivation that invites listeners to turn complaints into smiles, and realize that many other people are also facing difficulties. The importance of intrapersonal communication in managing emotions and helping individuals deal with problems in a more positive way. Keywords: Intrapersonal Communication, Andemesh Kamaleng, Smile, Motivation